Pathogenic Fungi Associated with Coriander Wilt Disease: Cultural Condition, Molecular Identification and Biological Control (Plant Tissue Culture and Biotechnology, 2025)
The study was undertaken to identify the causal pathogen of the wilt disease of coriander and explore its cultural conditions, molecular characterization and biological control through antagonistic fungi and plant extracts. The wilt disease of coriander has been linked to the pathogenic fungus Fusarium oxysporum. The isolated F. oxysporum ITS region yielded 507 bp PCR results. Using the greatest parsimony method with 1000 bootstrapping, a phylogenetic tree of 27 strains of F. oxysporum based on their ITS nucleotide sequences revealed 100% identification with PP506640.1, JUF0083 (F. oxysporum). The findings indicated that PDA medium (75 mm) was the most effective culture medium, followed by PSA medium (72 mm) and the lowest growth (40 mm) was found in YEA medium. The ideal pH and temperature were 6.5 and 25°C, respectively for F. oxysporum mycelial growth. The highest inhibition was showed by T. harzianum (75%), followed by T. erinaceum (63%) and lowest inhibition was showed by T. asperellum (55%) against mycelium growth and development of F. oxysporum. The plant extract of Azadirechta indica provided the highest inhibition rate (70%) followed by Lawsonia inermis (69%) at 30% (v/v) concentration rate. The results suggested that antagonistic fungus, T. harzianum is an effective agent against F. oxysporum, a causal agent of coriander wilt disease.Plant Tissue Cult. & Biotech. 34(2): 193-204, 2024 (December)